Evaluation of oral and dental health results and competition stress levels of adolescent athletes in different winter sports branches - Sevindik, B.; Sengül, F.; Kiyici, F. (The Eurasian Journal of Medicine, 2024)
Background: The aim of the present study was to examine the findings of the intraoral examinations of the 12-16 years old novice (control) and elite athletes across the winter sports branches, which were alpine discipline skiing, snowboarding, biathlon, ski jumping, and ice hockey. Besides, the study aimed to determine the intra- and inter-group relationships by comparing the athletes salivary stress biomarker levels at pre competition, during-match, and post-competition stages.